Threshold values determination in high-voltage equipment diagnosis insulation by registration methods of partial discharges - A. A. Kuznetsov; A. Yu. Kuzmenko; M. A. Kuznetsova; A. V. Simakov (Омский научный вестник)
The paper presents theoretical information diagnosing insulation parameters of high-voltage transformers. The results of experimental studies on high-voltage transformers in the normal, pre-emergency and emergency states are shown. The comparison was made with the data of chromatographic analysis to determine the threshold values according to the results of acoustic control.